2022
DOI: 10.1101/2022.02.17.480819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metagenomic analysis reveals the abundance and diversity of opportunistic fungal pathogens in the nasopharyngeal tract of COVID-19 patients

Abstract: The nasopharyngeal tract (NT) of human is a habitat of a diverse microbial community that work together with other gut microbes to maintain the host immunity. In our previous study, we reported that SARS-CoV-2 infection reduces human nasopharyngeal commensal microbiome (bacteria, archaea and commensal respiratory viruses) but increases the abundance of pathobionts. This study aimed to assess the possible changes in the resident fungal diversity by the inclusion of opportunistic fungi due to the infection of SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 76 publications
(129 reference statements)
0
4
0
Order By: Relevance
“…increased in the lower airway in more severe COVID-19 patients [69,71]. Contrary to the bacterial microbiome, Hoque et al found increased alpha diversity in the fungal microbiome of nasopharyngeal swabs in COVID-19 relative to healthy controls [84]. Nasopharyngeal fungal microbiome studies may be especially interesting since in addition to lung infection, Mucor spp.…”
Section: Associations Of Covid-19 With Microbial Constituents Other T...mentioning
confidence: 99%
“…increased in the lower airway in more severe COVID-19 patients [69,71]. Contrary to the bacterial microbiome, Hoque et al found increased alpha diversity in the fungal microbiome of nasopharyngeal swabs in COVID-19 relative to healthy controls [84]. Nasopharyngeal fungal microbiome studies may be especially interesting since in addition to lung infection, Mucor spp.…”
Section: Associations Of Covid-19 With Microbial Constituents Other T...mentioning
confidence: 99%
“…However, studies have shown that there is variation in animal susceptibility to feed induced acidosis and the severity of the pH depression required to cause SARA symptoms varies among cows (11-13). Gene expression-based biomarkers have been investigated as predictive biomarker for disease detection (14)(15)(16). These biomarkers carry the high potential as an alternative to or to be used in conjunction with ruminal pH measurement for early diagnosis or prevention of acidosis.…”
Section: Introductionmentioning
confidence: 99%
“…
Introduction: With the goal to maximize intake of high-fermentable diet needed to meet energy needs during weaning period, calves are at risk for ruminal acidosis. Using the calves from previously established model of feed-induced, ruminal acidosis in young calves, we aimed to investigate the changes in rumen epimural transcriptome and its microbial metatranscriptome at weaning (8week) and post-weaning (17-week) in canulated (first occurred at 3 weeks of age) Holstein bull calves with feed-induced subacute ruminal acidosis.Methods: Eight bull calves were randomly assigned to acidosis-inducing diet (Treated, n = 4; pelleted, 42.7% starch,15.1% neutral detergent fiber [NDF], and 57.8% nonfiber carbohydrates), while texturized starter was fed as a control (Control, n = 4; 35.3% starch, 25.3% NDF, and 48.1% nonfiber carbohydrates) starting at 1 week through 17 weeks. Calves fed acidosis-inducing diet showed significantly less (p < 0.01) body weight over the course of the experiment, in addition to lower ruminal pH (p < 0.01) compared to the control group.
…”
mentioning
confidence: 99%
See 1 more Smart Citation